2021
DOI: 10.3889/oamjms.2021.7534
|View full text |Cite
|
Sign up to set email alerts
|

Nanomembrane-based Apheresis as Safe and Effective Therapy for Cytomegalovirus and Epstein-Barr Virus Reactivation

Abstract: BACKGROUND: Heavy training schedules or endurance competitions in marathon are forms of extreme physical stress and lead to immunodepression in runners which could be associated with increased susceptibility to viral reactivation by ubiquitous viral infection such as cytomegalovirus (CMV) and Epstein-Barr virus (EBV). Lately, it was confirmed presence of elevated CMV and EBV loads and the lower antibody titers in competitive athletes. The most common clinical features are fatigue and adynamia accompanied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…These filters are produced in a way that preserves blood cells not only by pore size but also by their rounded edges [25]. However, our results indicated that LVPE may affect inflammatory and coagulation pathways through a significant decrease in SE, platelet count, and mean platelet volume (MPV).…”
Section: Discussionmentioning
confidence: 76%
“…These filters are produced in a way that preserves blood cells not only by pore size but also by their rounded edges [25]. However, our results indicated that LVPE may affect inflammatory and coagulation pathways through a significant decrease in SE, platelet count, and mean platelet volume (MPV).…”
Section: Discussionmentioning
confidence: 76%
“…Novel nanomembrane-based technology was approved by the American Society for Apheresis as a minimally invasive treatment. It is characterized by rapid control of quantitative and qualitative abnormalities of plasma and blood components using a semi-permeable nanomembrane that localizes immunologically active compounds on its surface [ 15 ]. According to the American Academy of Neurology 2011 plasmapheresis guidelines, there is insufficient evidence to support or refute the use of plasmapheresis for MG [ 7 ].…”
Section: Introductionmentioning
confidence: 99%